Metagenomic next-generation sequencing of cerebrospinal fluid: a diagnostic approach for varicella zoster virus-related encephalitis - Tang, Jin; Wang, Kaimeng; Xu, Haoming; Han, Jingzhe (Frontiers in Cellular and Infection Microbiology, 2024)
PurposeVaricella zoster virus-related encephalitis (VZV-RE) is a rare and often misdiagnosed condition caused by an infection with the VZV. It leads to meningitis or encephalitis, with patients frequently experiencing poor prognosis. In this study, we used metagenomic next-generation sequencing (mNGS) to rapidly and accurately detect and identify the VZV pathogen directly from cerebrospinal fluid (CSF) samples, aiming to achieve a definitive diagnosis for encephalitis patients.MethodsIn this retrospective study, we analyzed the clinical characteristics and laboratory evaluations of 28 patients at the Harrison International Peace Hospital in Hebei, China, between 2018 and 2024. These patients were diagnosed with neurological disorders using mNGS techniques applied to CSF.ResultsIn this cohort of 28 patients, 11 were females and 17 males, with a median age of 65 (IQR: 42.3-70). VZV-RE presented with a range of clinical manifestations, the most common being headaches (81.2%), fever>38°C (42.9%), and vomiting (42.9%). Less frequent symptoms include personality changes (10.7%), speech impairments (21.4%), cranial nerve involvement (21.4%), altered consciousness (17.9%) and convulsions (3.6%). Herpes zoster rash was observed in 35.7% of the cases. Neurological examination revealed nuchal rigidity in only 5 patients. CSF analysis indicated mild pressure and protein levels increase, with all patients having negative bacterial cultures. Abnormal electroencephalogram (EEG) findings were noted in 10.7% (N=3), and encephalorrhagia on Magnetic Resonance Imaging (MRI) was observed in 3.6%. VZV-RE was confirmed through mNGS analysis of CSF within three days of admission. All patients received empiric treatment with acyclovir or valacyclovir, with 21.4% receiving hormonotherapy, and 7.14% receiving immunoglobulin therapy. At the three-month follow-up, 10.7% of the patients had persistent neurologic sequelae, and the mortality rate was 3.6%.ConclusionsPerforming mNGS on CSF offers a rapidly and precisely diagnostic method for identifying causative pathogens in patients with VZV central nervous system (CNS) infections, especially when traditional CNS examination results are negative. Furthermore, the cases reported highlight the positive therapeutic effect of ganciclovir in treating VZV infections.